2021
DOI: 10.1111/tbj.14297
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic difficulties of men with breast cancer

Abstract: Most adequately powered studies confirm a worse prognosis for males versus matched females with breast cancer. There is in‐stage migration for stage I cancers with a different ratio of tumor/normal breast tissue in males. Younger men have a better prognosis, largely the result of increased morbidity in the elderly, exacerbated by smoking, low socioeconomic differences, and ethnic disparity. BRCA2 carriers with MBC have a worse outcome than noncarriers as do men with amplification of EMSY. Men with tumors havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…The incidence of MBC had a similar increasing rate with that of female breast cancer, which is probably related to the popularity of mammography screening ( 5 , 6 ). However, it was shown that the prognosis of MBC patients was worse than that of female breast cancer patients ( 7 9 ). Similar to female breast cancer, the incidence of MBC also has regional differences, which is higher in North America and Europe and lower in Asia ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of MBC had a similar increasing rate with that of female breast cancer, which is probably related to the popularity of mammography screening ( 5 , 6 ). However, it was shown that the prognosis of MBC patients was worse than that of female breast cancer patients ( 7 9 ). Similar to female breast cancer, the incidence of MBC also has regional differences, which is higher in North America and Europe and lower in Asia ( 10 ).…”
Section: Introductionmentioning
confidence: 99%